Preparation and Characterization of Electrospun Polycaprolactone Nanofiber Webs Containing Water-soluble Eggshell Membrane and Catechin (Journal of Fiber Bioengineering and Informatics, 2012)
The process of incorporating water-soluble Eggshell Membrane (S-ESM) into Polycaprolactone (PCL)electrospun nanofiber webs was investigated, utilizing the hydrogen bonding interaction between S-ESM and catechin. PCL was first electrospun with catechin, and S-ESM was introduced into theresulting PCL/catechin nanofibers by immersing the fibers in S-ESM solution. Morphological observationsuggested that S-ESM was incorporated with catechin and formed S-ESM/catechin nanoparticles,distributed in the PCL nanofiber webs. Analysis of FTIR spectra indicated that hydrogen bondinginteractions were generated between PCL and catechin as well as between S-ESM and catechin. Thebulk compression property of electrospun nanofiber webs was measured and the results showed S-ESMand catechin had effect on modifying the mechanical property of PCL nanofiber webs.
Keywords: Water-soluble Eggshell Membrane; Catechin; Nanofiber; Compression